1999
DOI: 10.1177/107602969900500303
|View full text |Cite
|
Sign up to set email alerts
|

The G20210A Polymorphism in the 3' -Untranslated Region of the Prothrombin Gene in Mexican Mestizo Patients with Primary Antiphospholipid Syndrome

Abstract: In an effort to identify alleles associated with an increased risk of venous thrombosis in patients with primary antiphospholipid syndrome, we studied the G20210A polymorphism (the G-->A mutation at nucleotide position 20210) in the 3'-untranslated region of the prothrombin gene in a group of 14 patients with primary antiphospholipid syndrome. We did not find any patient with the mutated gene. Since the prothrombin mutation is more prevalent in white populations, this finding may be related with the genetic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…This polymorphism was found to be rare in patients with APS and several studies have not shown positive association between thrombosis in APS patients and this polymorphism [34][35][36].…”
Section: Additional Genetic Risk Factorsmentioning
confidence: 93%
“…This polymorphism was found to be rare in patients with APS and several studies have not shown positive association between thrombosis in APS patients and this polymorphism [34][35][36].…”
Section: Additional Genetic Risk Factorsmentioning
confidence: 93%
“…The initial studies did not show an increased risk of thrombosis related to the G20210A polymorphism in the prothrombin gene in APS patients of Caucassian (Bentolila et al, 1997); (Bertolaccini et al, 1998) or Mexican mestizo origin (Ruiz-Arguelles et al, 1999). However, from the first case of SLE-associated APS in a young female homozygous for the 20210A allele in the prothrombin gene who developed venous thrombosis while taking oral contraceptives (Sivera et al, 2000), several subsequent studies have demonstrated an association between the prothrombin G20210A polymorphim and thrombosis in APS patients.…”
Section: Prothrombin Gene Mutation and Risk Of Thrombosismentioning
confidence: 98%
“…Avivi et al [44] found elevated plasma homocyteine levels in onethird of APS patients, Seriolo et al [45] demonstrated that plasma homocyteine levels are significantly higher in aPLpositive rheumatoid arthritis (RA) patients with thrombosis compared with aPL-positive RA patients without thrombosis, and Ames et al [46,47] suggested that higher plasma homocysteine levels and methylenetetrahyrofolate reductase (MTHFR) mutation may influence the age of first event and the number of events in aPL-positive patients. Torresan et al [48] suggested that prothrombin (Factor II) G20210 mutation increases the risk for thrombosis in aPL-positive patients, a finding was not supported by other studies [49,50]. In addition, Torresan et al [48] reported that FVL mutation, MTHFR mutation, or protein C, protein S, and antithrombin III deficiencies are not associated with increased risk for thrombosis in aPL-positive patients.…”
Section: Introductionmentioning
confidence: 95%